Study Of Axial Length In Retinal Vein Occlusions (International Journal of Scientific Research and Management (IJSRM), 2015)
Retinal vein occlusion is the most common retinal occlusive disorder encountered by ophthalmologists and is usually associated with a variable amount of visual loss.RVO most commonly affects the venous blood supply of the entire retina, central retinal vein occlusion (CRVO) or a quadrant by one of the branches, Branch retinal vein occlusion (BRVO). Less commonly the superior or inferior half of the retina alone is affected, Hemi retinal vein occlusion.